Interleukin-5 induces apoptotic defects in CD4+ T cells of patients with allergic rhinitis. Issue 4 (29th January 2019) - Luo, Xiang-Qian; Ma, Fei; Wang, Shuai; Zhao, Mei-Zhen; Shao, Jian-Bo; Geng, Xiao-Rui; Liu, Jiang-Qi; Mo, Li-Hua; Guan, Li; Liu, Zhi-Gang; Liu, Da-Bo; Yang, Ping-Chang
Abstract: T helper (Th)2 polarization plays an important role in the pathogenesis of allergic diseases; the underlying mechanism remains to be further investigated. B cell lymphoma protein-2 like protein-12 (Bcl2L12) has the anti-apoptotic function. This study aims to elucidate the contribution of Bcl2L12 to Th2 polarization in patients with allergic rhinitis (AR). In this study, human CD4 + T cells were isolated from blood samples collected from AR patients and healthy control (HC) subjects. The immune response profiles of CD4 + T cells were analyzed by immunologic approaches. The results showed that AR CD4 + T cells (CD4 + T cells collected from AR patients) showed defects of apoptosis. The expression of FasL in AR CD4 + T cells was lower than that of HC CD4 + T cells. Serum IL-5 levels were negatively correlated with the expression of FasL in AR CD4 + T cells. Exposure of CD4 + T cells to IL-5 in the culture suppressed the expression of FasL and increased the expression of Bcl2L12. IL-5 increased the levels of Bcl2L12 in CD4 + T cells, the latter bound to the FasL promoter to prevent FasL gene transcription. Inhibition of Bcl2L12 restored the apoptosis machinery in AR CD4 + T cells. In conclusion, overexpression of Bcl2L12 in CD4 + T cells compromises the apoptosis machinery; the latter can be restored by inhibition of Bcl2L12. BcL2L12 in CD4 + T cells may be a novel target for the treatment of AR and other allergic disorders. Graphical Abstract: CD4 + T cells express Bcl2L12, which restricts FasL expression and induces apoptotic defects in CD4 + T cells.